2023
DOI: 10.1371/journal.pone.0279097
|View full text |Cite
|
Sign up to set email alerts
|

Semantic segmentation of UAV remote sensing images based on edge feature fusing and multi-level upsampling integrated with Deeplabv3+

Abstract: Deeplabv3+ currently is the most representative semantic segmentation model. However, Deeplabv3+ tends to ignore targets of small size and usually fails to identify precise segmentation boundaries in the UAV remote sensing image segmentation task. To handle these problems, this paper proposes a semantic segmentation algorithm of UAV remote sensing images based on edge feature fusing and multi-level upsampling integrated with Deeplabv3+ (EMNet). EMNet uses MobileNetV2 as its backbone and adds an edge detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Li, X. et al found that small objects tend to be overlooked when applying Deeplabv3+ to drone datasets. As a result, they proposed EMNet, which is based on edge feature fusion and multi-level upsampling [25]. Wang, X. et al achieved promising results when applied to high-resolution remote sensing images using a joint model constructed from improved UNet and SegNet [26].…”
Section: Dcnn In the Remote Sensing Domainmentioning
confidence: 99%
“…Li, X. et al found that small objects tend to be overlooked when applying Deeplabv3+ to drone datasets. As a result, they proposed EMNet, which is based on edge feature fusion and multi-level upsampling [25]. Wang, X. et al achieved promising results when applied to high-resolution remote sensing images using a joint model constructed from improved UNet and SegNet [26].…”
Section: Dcnn In the Remote Sensing Domainmentioning
confidence: 99%
“…The generator [5,30,31] receives a multifaceted input comprising various components: an initial frame image, an intermediary frame image, a concluding frame image, and their corresponding labeled image. In this study, due to the relative displacement of the UAV when photographing the buildings, the external shape of the buildings does not change with its movement; therefore, we classify this 'building movement' as rigid motion, leading us to adopt an optical flow model with a uniform smoothing strategy.…”
Section: Semi-supervised Optical Flow Estimation Channel In Dual-chan...mentioning
confidence: 99%
“…On considering the documented behaviour of the beluga whale in human care, the beluga whale has performed the social-sexual mannerism under various postures like pair swims of two BW, which is closely together with the mirrored manner. Hence, the location of the searching agents is determined through the pair swim of BW as well as the location of the beluga whale is updated as given in Eq (11).…”
Section: Plos Onementioning
confidence: 99%
“…As inspired by FCN, a variety of structures and techniques have been recommended to enhance the semantic segmentation process to next level like encoder-decoder architecture using SegNet, DeepLabv2 and spatial pyramid pooling structure on the PSPNet and DeepLabv3+ for semantic segmentation of UAV remote sensing images based on edge feature fusing and multilevel upsampling. Being diverse from the multimedia images, the higher resolution aerial images generally cover a larger area as well as include complex scenes that have brought limitations to the semantic segmentation tasks [ 11 ]. In another case, the high-resolution aerial images also contain rich geographical details like Digital Surface Model (DSM).…”
Section: Introductionmentioning
confidence: 99%